CHANGES IN CHEMICAL PROPERTIES BY USE AND MANAGEMENT OF AN OXISOL IN THE AMAZON BIOME - Rodrigues, Marcos (2017)
The proper soil use and management are essential for a sustainable production, thus the pursuit for systems that minimize damages to the environment and improve soil fertility is continuous. The objective of this study was to evaluate changes in soil fertility by the use and management of an Oxisol (Latossolo Vermelho-amarelo, SiBCS) in the Amazon biome. The soil uses and management systems evaluated were native forest, native pasture, minimum tillage system and conventional tillage system. The chemical atributes of the soil layers 0.00-0.10, 0.10-0.20, 0.20-0.30 and 0.30-0.40 m were evaluated. The soil pH (CaCl2) and the contents of organic matter, available phosphorus and exchangeable potassium, calcium, magnesium and aluminum were evaluated and the saturation by Al, effective cation exchange capacity and soil potential were determined. The highest pH values were found in the native pasture area, and the highest exchangeable aluminum contents were found in the layers 0.00-0.10 and 0.10-0.20 m of the conventional tillage system. The highest phosphorus availability was found in the layer 0.00-0.10 m of the native forest area. The highest potassium availability was found in the minimum tillage system. The lowest calcium and magnesium values were found in the layers 0.00-0.10 and 0.10-0.20 m of the conventional tillage system. The highest soil organic matter content was found in the layer 0.00-0.10 m of the native forest area. The nutrient availability for plants decreases in soils managed using the conventional tillage system. Soil uses and management systems of little soil disturbance are recommended to minimize environmental degradation in the Amazon biome.